Attitude of Patients towards Anaesthesia: Comparing the Use of a Single Consent for Anaesthesia versus the Combined Surgical and Anaesthetic Consent. - Niew, YL; Chee, Magdalene MX; Juanita Joseph,; Nurul Ezzati AK,; Mohd Sharol AW,; Azarinah I,; Choy, YC (Department of Surgery, UKM Medical Centre, 2014)
Anaesthesiology is a specialty which is less well known and the public usually have little knowledge regarding anaesthesia and the roles of Anaesthesiologist. Many hospitals now use a single dedicated consent for anaesthesia. This study was conducted to compare the effectiveness of a single consent for anaesthesia with the combined surgical and anaesthetic consent. A total of 109 patients, scheduled for elective surgery requiring anaesthesia were interviewed with a standardised questionnaire. Patients were divided into two groups, where one group used a single anaesthetic consent while the other used a combined surgical and anaesthetic consent. A single consent for anaesthesia was found to be more effective than the current combined surgical and anaesthetic consent (p<0.05). Regarding information about anaesthesia, 89.91% respondents agreed that the Anaesthesiologist should tell them all material risks of anaesthesia, no matter how serious it is and 81.65% respondents would like to meet Anaesthesiologist every time prior to the operation. In terms of knowledge, 94.5% patients recognized that Anaesthesiologist is the one who delivers anaesthesia during surgery. However, patients had little knowledge regarding the extended roles of Anaesthesiologist. The present study confirmed that a single consent for anaesthesia was better than the current combined surgical and anaesthetic consent.